(untitled) (Asian Journal of Pharmaceutics (AJP), 2024)
Face serums are specialty skincare concoctions that target particular issues and produce noticeable results by deeply delivering powerful active ingredients into the skin. These thin, highly concentrated products are usually made with a combination of healthy ingredients such as retinol, hyaluronic acid, Vitamin C, or alpha-hydroxy acids. Depending on how they are made, face serums can have a wide range of effects, but they frequently have hydrate, anti-aging, brightening, exfoliating, soothing, and oil-control properties. You can address your specific skincare concerns and achieve healthier, more radiant skin by adding the right serum to your skincare routine. Over the past 10 years, the cosmetics industry has consistently expanded. The large and expanding youth population is one of the main factors driving growth in this category. Indian women today are more concerned with keeping their skin youthful and radiant by minimizing wrinkles and changing the color of their skin. This has led to an increase in the market for skin care products of all kinds. Like any other cream, serum is a highly concentrated product based on water or oil. A small number of ingredients in the serum are intended to maximize the availability of the active ingredient, which could be a growth factor, vitamin, botanical extract, etc. Because the serum has a lower viscosity, it absorbs more quickly and penetrates the skin’s deep layers to target different areas and provide the most nourishing skin. Face serums address a variety of skincare needs by providing hydration, anti-aging benefits, brightening effects, exfoliation, soothing qualities, and oil control. Face serums, which provide customized solutions for attaining healthier, more radiant skin, have become essential components of contemporary skincare routines due to their lightweight texture and potent efficacy. Photodamage and ultraviolet exposure can cause unwanted outcomes such as wrinkles on the face and aging of the skin. The deep formula of the serum has a high concentration of active ingredients, a non-greasy finish, quick absorption, and the capacity to penetrate the skin’s deep layers. The goal of the research was to create a serum using a polyhedral extract based on these features. Face serum is a highly concentrated cosmetic product made of olive oil, betel fruit extract, and Aloe vera gel. Face serum made with A. vera, bael fruit extract, and olive oil is a very potent cosmetic. A. vera serum can absorb quickly and penetrate deeper, which gives us immediate cosmetic benefits as well as psychological satisfaction.